Ethical Dilemma in Vaccination in Indonesia: Balance Between Public Health Obligations and Individual Autonomy Rights. - Rifqi, A. Ikram; Hertiana; Tubuon, Yulinda Novita; Hariani; Siti Rahma; Indar (Promotif : Jurnal Kesehatan Masyarakat, 2024)
Background: Vaccination is a biological product containing antigens that actively stimulate specific immunity against certain diseases. Before the COVID-19 pandemic, high vaccination coverage among children in Indonesia played a critical role in reducing morbidity from vaccine-preventable diseases. However, the pandemic disrupted the national immunization program, as UNICEF reports highlighted a decline in vaccination coverage due to mobility restrictions and parental concerns over COVID-19 exposure. This decline increased the risk of outbreaks of preventable diseases such as measles and diphtheria. The ethical dilemma of vaccination arises between the public health obligation to prevent disease spread and the individual autonomy to make personal health decisions, including vaccination. This study aims to identify the ethical challenges of vaccination in Indonesia, analyze the factors influencing public attitudes toward vaccines, and provide policy recommendations. Method: A literature review methodology was employed, encompassing articles in both Indonesian and English languages, with keywords including "vaccination ethics," "individual autonomy," "public health obligations," and "Indonesia." Result: The study findings highlight the tension between government efforts to achieve herd immunity and individual rights, as well as challenges in vaccine distribution in remote areas. Conclusion: In conclusion, vaccination policies in Indonesia should prioritize balancing public health interests and individual rights, emphasizing public education and strengthening vaccine distribution infrastructure.